Mite diversity, new species description and evaluation of phytoseiid mites as biological control agents of Aceria litchii (Keifer) (Acari: Eriophyidae) on litchi plants - Ferraz, Célia Siqueira (2017)
Aceria litchii (Keifer) (Acari: Eriophyidae) is considered one of the main pests of the litchi crop through the world. The control of this pest mite in the main production areas is done by pruning of the infested branches and application of pesticides. However, there is no pesticide registered in Brazil for control of this mite in the litchi crop and pruning is considered expensive by many growers. In addition, pesticides are often inefficient against most eriophyid mites since they frequently live under protective structures of the plant. This all reinforces the need of research for alternative control practices that are sustainable in the long term, such as biological control, which consists of the use of natural enemies to reduce the population density of pest species. Given this, initially, surveys were carried out in litchi orchards seeking natural enemy species with potential to control A. litchii. Later, two new species of the Iolinidae family, which were found during these survey, were described and illustrated. Then, two species from the Phytoseiidae family collected during the field survey were selected, Phytoseius intermedius Evans & MacFarlane and Amblyseius herbicolus (Chant), and the ability of these predators to control A. litchii in litchi plants was investigated under field conditions. Moreover, it was investigated whether the supplementation of the A. herbicolus population with alternative food (cattail pollen) could improve the control of A. litchii. Most of the mite species found belong to families that were predominantly predators. Phytoseiidae was the most diverse family of mites, with a total of 11 species. The two new species described and illustrated in the Iolinidae family were Pausia litchiae n. sp. and Pseudopronematulus nadirae n. sp.. Moreover, it was shown that the incidence of erinea on plants increased throughout the experiment on all treatments. In the same way, the pollen addition did not provide greater population growth for A. herbicolus on the litchi plants. In conclusion, these results showed the arthropod diversity found associated with the erinea induced by A. litchii, highlighting the large number of predatory mites. Furthermore, the description of the new species of mites in the Iolinidae family was also shown. In addition, it was observed that P. intermedius and A. herbicolus presented limitations to control the increase of the incidence of erinea induced by A. litchii.